Designing on screen - Baricevic, Thomas; Scoglio, Stephen; De Robbio, Michael; Video Education Australasia (Australia : Video Education Australasia, 2009)
Design is a wide ranging discipline that encompasses art, engineering, communications, web design, graphic design and many other areas. The use of information and communications technology can assist graphic designers throughout the design process. In this program we look at using ICT in design while applying different elements and processes to both student and professional scenarios
Executive producer, Simon Garner
DVD format
Keywords: Graphic arts; Computer-aided design; Design; Information technology